Localization and density of immune cells in the invasive margin of human colorectal cancer liver metastases are prognostic for response to chemotherapy - Halama, Niels; Michel, Sara; Kloor, Matthias; Zörnig, Inka; Benner, Axel; Spille, Anna; Pommerencke, Thora; Knebel Doeberitz, Magnus von; Folprecht, Gunnar; Luber, Birgit; Feyen, Nadine; Martens, Uwe M.; et al. (Cancer research, 2011)
Increasing evidence supports the concept that the interaction between a colorectal tumor and its local immune microenvironment dictates patient prognosis and treatment response.